Towards a universal model of family centered care: a scoping review - Kokorelias, Kristina M.; Gignac, Monique A. M.; Naglie, Gary; Cameron, Jill I. (BMC health services research, 2019)
Background Families play an important role meeting the care needs of individuals who require assistance due to illness and/or disability. Yet, without adequate support their own health and wellbeing can be compromised. The literature highlights the need for a move to family-centered care to improve the well-being of those with illness and/or disability and their family caregivers. The objective of this paper was to explore existing models of family-centered care to determine the key components of existing models and to identify gaps in the literature. Methods A scoping review guided by Arksey & O’Malley (2005) examined family-centered care models for diverse illness and age populations. We searched MEDLINE, PsycINFO, CINAHL and EMBASE for research published between 1990 to August 1, 2018. Articles describing the development of a family-centered model in any patient population and/or healthcare field or on the development and evaluation of a family-centered service delivery intervention were included. Results The search identified 14,393 papers of which 55 met our criteria and were included. Family-centered care models are most commonly available for pediatric patient populations ( n = 40). Across all family-centered care models, the consistent goal is to develop and implement patient care plans within the context of families. Key components to facilitate family-centered care include: 1) collaboration between family members and health care providers, 2) consideration of family contexts, 3) policies and procedures, and 4) patient, family, and health care professional education. Some of these aspects are universal and some of these are illness specific. Conclusions The review identified core aspects of family-centred care models (e.g., development of a care plan in the context of families) that can be applied to all populations and care contexts and some aspects that are illness specific (e.g., illness-specific education). This review identified areas in need of further research specifically related to the relationship between care plan decision making and privacy over medical records within models of family centred care. Few studies have evaluated the impact of the various models on patient, family, or health system outcomes. Findings can inform movement towards a universal model of family-centered care for all populations and care contexts.